Kajian Hukum Islam Atas Produksi Dan Distribusi Produk Kulit Dalam Industri Rumahan Di Sukaregang Kabupaten Garut - Syaripudin, Enceng Iip; Fauzi, Fauzi (Jurnal Hukum Ekonomi Syariah, 2025)
This study aims to examine the production and distribution of leather products in the home industry of Sukaregang, Garut Regency, from the perspective of Islamic law. The home industry producing leather products, such as bags, shoes, and other accessories, has been growing in this region and significantly impacts the local economy. However, these production and distribution practices need to be evaluated from a sharia perspective, particularly concerning the halal status of raw materials, production processes, commercial transactions, and worker welfare. In Islam, leather products must comply with halal principles, including adherence to proper animal slaughtering methods, the use of halal-certified chemicals, and environmentally friendly waste management. Additionally, business transactions in this industry must align with principles of fairness and transparency, avoiding elements of fraud or usury. This study also highlights the importance of local economic empowerment through home industries that prioritize worker welfare and sustainable resource management. Using a qualitative approach, this research analyzes relevant aspects of Islamic law and provides recommendations for improving leather production and distribution practices in accordance with sharia principles. The findings are expected to contribute to the development of a sustainable and responsible home leather industry in Sukaregang, Garut Regency. Keywords: Islamic Law; production; distribution; home industry; Sukaregang Garut